The Starting Lineup: Key Microbial Players in Intestinal Immunity and Homeostasis - Reading, Nicola C.; Kasper, Dennis L. (Frontiers in Microbiology, 2011)
The complexity of microbiota inhabiting the intestine is increasingly apparent. Delicate balance of numerous bacterial species can affect development of the immune system, how susceptible a host is to pathogenic organisms, and the auto-inflammatory state of the host. In the last decade, with the increased use of germ-free mice, gnotobiotic mice, and animal models in which a germ-free animal has been colonized with a foreign microbiota such as humanized mice, it has been possible to delineate relationships that specific bacteria have with the host immune system and to show what role they may play in overall host health. These models have not only allowed us to tease out the role of each individual species, but have also allowed the discovery and characterization of functionally unknown organisms. For example, Segmented Filamentous Bacteria (SFB) have been shown to play a vital role in expansion of IL-17 producing cells. Prior to linking their key role in immune system development, little was known about these organisms. Bacteroides fragilis can rescue some of the immune defects of gnotobiotic mice after mono-colonization and have anti-inflammatory properties that can alleviate colitis and experimental allergic encephalitis in murine models. Additionally, Clostridium species have most recently been shown to expand regulatory T-cell populations leading to anti-inflammatory conditions. This review will highlight and summarize some of the major findings within the last decade concerning the role of select groups of bacteria including SFB, Clostridium, Bacteroides, Bifidobacterium, and Lactobacillis, and their impact on host mucosal immune systems.